Enhancing liquid biopsies are a promising approach for the early detection of cancer - Rongyang Xu; Chengying Huang; Qiuming Pan; Ye Zhu; Shanqiang Qu (Acta Materia Medica)
Cancer is a formidable threat to human life, a cure for which in advanced stages remains challenging. Early detection and treatment of cancer are paramount, yet a substantial number of cancer patients receive diagnoses at an advanced stage, resulting in a lower 5-year survival rate. Early-stage cancers, however, frequently elude detection. Conventional tumor screening techniques, such as tumor biopsy, serve as essential means for an early cancer diagnosis. However, these procedures are invasive and may inadvertently facilitate cancer metastasis. A current research focal point involves liquid biopsy technologies, offering a potential solution to mitigate the above-mentioned issues, but often exhibiting low sensitivity. A research team from the Massachusetts Institute of Technology has recently pioneered an innovative approach to enhance the sensitivity of liquid biopsy for cancer diagnosis. By administering a pre-treatment agent 1–2 h prior to sampling, a greater than 10-fold increase in collected ctDNA was obtained. Subsequent tumor analysis using ctDNA not only demonstrated heightened sensitivity in detecting small tumors (>75%) but also presented a promising avenue for early clinical cancer detection and diagnosis. This discovery holds significant potential for advancing the prospects of early cancer detection, diagnosis, and treatment.